Analysis of the Impact of Budget Rationalization on the Work Program of the Wonosobo Regency DPRD Secretariat - Bayanah, Nuzilatul; Prakoso, Lukman Yudho (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Wonosobo Regency DPRD Secretariat is one of several government agencies in Wonosobo Regency that is experiencing budget rationalization. The aim of the research was to analyze the impact of budget rationalization on the Wonosobo Regency DPRD Secretariat Work Program. This research uses a descriptive and qualitative approach, with data collection techniques, namely interviews and observations conducted with several employees at the Wonosobo Regency DPRD Secretariat, and carrying out documentation. This research method shows that budget rationalization not only has implications for reducing the expenditure budget of the Wonosobo Regency DPRD Secretariat, but also has an impact on postponing or canceling work programs that have been prepared in the previous period. So the implementation of several work programs or activities had to be postponed.